Finite Time Stability of 2D Fractional Hyperbolic System with Time Delay. (27th May 2022) - Ben Makhlouf, Abdellatif; Arfaoui, Hassen; Boulaaras, Salah; Dhahri, Slim
Abstract : In this work, a class of two-dimensional fractional hyperbolic differential linear system (2D-FHDLS) with time delay is investigated. By using generalized Gronwall's inequality, sufficient conditions for the finite time stability (FTS) of two-dimensional fractional hyperbolic differential system with time delay are given. Numerical examples are also given to illustrate the stability result.